2020
DOI: 10.1080/23322039.2020.1751487
|View full text |Cite
|
Sign up to set email alerts
|

Does Infrastructural Absorptive Capacity Stimulate FDI-Growth Nexus in ECOWAS?

Abstract: The study assesses the relevance of infrastructural absorptive capacity in the foreign direct investment (FDI)-growth argument in ECOWAS. Though foreign aid has received a vast attention in the literature, however, an assessment of how the infrastructural readiness of the host economies drives the effectiveness of aid was vocal in this re-examination. The study assesses this main thrust in ECOWAS Sub-region for the period 1995-2017 using the system GMM estimation approach. The result suggests that FDI promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Besides, some recent studies in the extant literature (e.g. Saidi et al 2018 ; Maji and Waziri 2020 ; Ogundipe et al 2020 ; Cheng et al 2020 ) support the use of system GMM technique in investigating infrastructure–growth relationships.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Besides, some recent studies in the extant literature (e.g. Saidi et al 2018 ; Maji and Waziri 2020 ; Ogundipe et al 2020 ; Cheng et al 2020 ) support the use of system GMM technique in investigating infrastructure–growth relationships.…”
Section: Methodsmentioning
confidence: 93%
“…This study shows that there could be substantial regional differences on the growth effects of transport infrastructure. Ogundipe et al ( 2020 ) used GMM regression to investigate the role of road infrastructure on foreign direct investment (FDI) influx in ECOWAS and found that the responsiveness of FDI to physical infrastructures and the responsiveness of economic growth to road infrastructures declined.…”
Section: An Overview Of the Empirical Literaturementioning
confidence: 99%
“…he FDI-economic growth relationship raises important institutional issues on the recipient economy (Adegboye et al, 2020c;Ogundipe et al, 2020). Considering the capital-deficient nature of sub-Saharan African (SSA) economies overtime and the accruable benefits from external investor's activities, FDI is recognized as an essential factor in Africa's growth as well as development.…”
mentioning
confidence: 99%
“…Saidi et al (2018) employed the GMM technique to validate positive correlations among transport energy consumption, transport infrastructure, and economic growth in Middle Eastern and North African countries. Utilizing similar methodology, Ogundipe et al (2020) highlighted declining responsiveness of foreign direct investment to physical infrastructure and economic growth to road infrastructures within the Economic Community of West African States. Using dynamic spatial modeling, Wang et al (2020) showcased the significance of transport infrastructure for boosting economic growth in Brazil, Russia and India.…”
Section: Literature Reviewmentioning
confidence: 99%